KOMITEMEN MAHASISWA POLINEMA TERHADAP AL-QUR’AN SEBAGAI LANDASAN WIRAUSAHA YANG SUKSES - Fadloli Fadloli; Sri Nurkudri; Abdul Chalim (Politeknik Negeri Malang, 2017)
This study aims to find out about the commitment of Polinema students to the Qur'an. This research uses qualitative approach, making the students and lecturers of Islam as a source of information (human resource), supported by document resource, in the form of books and documents of Islamic education policy and the phenomenon of resources, in the form of religious activities. In order to obtain correct and correct information and data, we use participant observation method, documentation and question and answer, with description analysis. From the data analysis, the description shows that the Malang State Polytechnic students have a good commitment to the Qur'an, evidenced by the ownership of manual or digital al-Qur'an; in reading al-Qur'an, student 98% can read of State Polytechnic in Malang, this is supported by mentoring program for new students guidance of reading al-Qur'an in groups, but who memorized the Qur‟an a bit. Its understanding of the Qur'an is still textual and balanced with the study of the Qur'an in the mosque; while the implementation of the Qur'an is quite good, evidenced by the implementation of prayers in congregation at the campus mosque; fasting Romadhan well done; spending money (infaq and sodaqah) for solidarity and fostering the village is done by opening a charity box that is circulated in class and place in mosque. While the style of dress for a student with a standard qur'ani, covering the body and veil.